Kabuki plays on stage (University of Hawai'i Press, 2002)
The fourteen plays translated in Volume 3, Darkness and Desire, 1804-1864, mark an extreme point in the development of kabuki dramaturgy. The plays are remarkable, even within kabuki, for their intense theatricality, gutsy individualism of character, cold-blooded and ferocious violence, realism pushed into fantasy and grotesquery, novelty for its own sake, sexual aggressiveness, and assertion of female will. The plays depict a society in extremis, the end of an era, a time often marked by unmitigated darkness and desire.